2018
DOI: 10.1080/19420889.2018.1433441
|View full text |Cite
|
Sign up to set email alerts
|

Multiple lines of inhibitory feedback on AKT kinase in Schwann cells lacking TSC1/2 hint at distinct functions of mTORC1 and AKT in nerve development

Abstract: During nerve development, Schwann cells (SCs) build multilayered myelin sheaths around axons to accelerate nerve conduction. The mechanistic target of rapamycin complex 1 (mTORC1) downstream of PI3K/AKT signaling lately emerged as a central anabolic regulator of myelination. Using mutant mice with sustained mTORC1 hyperactivity in developing SCs we recently uncovered that mTORC1 impedes developmental myelination by promoting proliferation of immature SCs while antagonizing SC differentiation. In contrast, mTOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…This contradictory temporal pattern provided motivation to generate mice with disrupted tuberous‐sclerosis‐complex (TSC) complex components or upstream PTEN (phosphatase and tensin homolog) to induce different levels of sustained mTORC1 hyperactivity, in order to counteract the physiological mTORC1 decline in SC precursors during nerve development. The characterization of the developmental nerve phenotypes in these mutants led to the surprising conclusion that mTORC1 activity clearly impedes myelin formation by promoting the proliferation of immature SCs and blocking SC differentiation during nerve development . This finding was subsequently confirmed by two other studies .…”
Section: Mtorc1 Promotes Schwann Cell Proliferation or Myelinogenesismentioning
confidence: 64%
“…This contradictory temporal pattern provided motivation to generate mice with disrupted tuberous‐sclerosis‐complex (TSC) complex components or upstream PTEN (phosphatase and tensin homolog) to induce different levels of sustained mTORC1 hyperactivity, in order to counteract the physiological mTORC1 decline in SC precursors during nerve development. The characterization of the developmental nerve phenotypes in these mutants led to the surprising conclusion that mTORC1 activity clearly impedes myelin formation by promoting the proliferation of immature SCs and blocking SC differentiation during nerve development . This finding was subsequently confirmed by two other studies .…”
Section: Mtorc1 Promotes Schwann Cell Proliferation or Myelinogenesismentioning
confidence: 64%
“…3 . In mammalian PNS, GFs perform their biological actions of promoting intrinsic neurite outgrowth and synaptic plasticity by working together with PI3K/Akt signaling [ 79 ]. Furthermore, previous research has demonstrated that NGF-induced PI3K/Akt activation occurs through binding the TrkA receptor rather than p75 NTR to promote neurite outgrowth and neuronal survival in cultured primary neurons [ 80 ].…”
Section: Gf Signaling Mechanisms That Regulate Nerve Regenerationmentioning
confidence: 99%
“…Although neither of the aberrant Fbxw7 mutant SC-axon interaction phenotypes have been previously described in vivo, several of the other phenotypes observed in Fbxw7 mutant nerves resemble phenotypes described in mutants where mTOR signaling is enhanced such as in Pten mutants [14] and constitutively active Akt mutants [15]. It is well documented, from these studies and others, that mTOR levels must be tightly regulated in SCs such that any type of manipulation results in defective PNS myelination [14,15,[19][20][21][22][23][24][25]. mTOR is a bona fide target of Fbxw7 in other contexts [16] and Fbxw7 was recently shown to control OL myelination through mTOR [7].…”
Section: Discussionmentioning
confidence: 79%